Development of Electronic Book (E-Book) EPUB-Based for Display Course - Lailatul Maulindah; Mohammad Arief; Mariani Setijo Oetami (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The purpose of this research are generating module of administration facilities and infrastructure based learning cycle 5E for students of SMK/MAK grade XII Office Administration skill program, determine the feasibility module of administration facilities and infrastructure based learning cycle 5E through expert validation test modules, subject matter experts, and students, also to determine improving student learning outcomes before and after using the module of administration facilities and infrastructure based learning cycle 5E. The result of research show that the development result module is deemed very feasible to be used in the learning activities and the average student score after using the development result module also experience an increase.